Islamic educational values reflected in the traditional sandur dance: A case study in gentansari - Yunita Sari; Luluk Ifadah; Nur Alfi Muanayah; Ruslan Agus (Yayasan Azhar Amanaa Yogyakarta, 2025)
The background in this article is the application of traditional Islamic boarding schools. Learning methods. The purpose of writing this article is to explain learning methods. Traditional Islamic boarding schools, explain the various learning methods in traditional Islamic boarding schools and explain the advantages of the methods used by these Islamic boarding schools. This article uses library research methods so that in this article the researcher takes data from related literature For this research. The data in this article is presented descriptively, namely presentation in form Writings that have been studied in depth. The results of this research explain the application of learning Methods used in traditional Islamic boarding schools. There is a need to develop The learning model in Islamic boarding schools is by using a better learning method, namely using. More effective method in the classroom, planning and implementing activities in such a way continuously and Also through group work.